Solid-liquid mass transfer in a Peirce-Smith converter: A physical modelling study - Chibwe, D.; Akdogan, G.; Eksteen, Jacques (Nauchno-Issledovatel'skii Institut Ukrmetallurginform, 2011)
Pyro-metallurgical processes are multiphase in nature involving gas-liquid-solid interactions. In the Peirce-Smith converter operation, the additions of cold solids in liquid matte in the form of fluxing agents (silica sands) for slag liquidity, process scrap and reverts for temperature control is a common practice. It is reasonable to postulate that with such practice, solid-liquid mass transfer step may play an important role in the performance and attainment of liquid bath homogeneity of the process. In this work, solid additions were simulated with sintered benzoic acid compacts spatially positioned in a 1:5 water model of a Peirce-Smith converter. Water and kerosene were used to simulate matte and slag respectively. Solid-liquid mass transfer was characterized by experimentally determined mass transfer coefficient, K (ms-1) values of benzoic acid sintered compacts and calculated dimensionless turbulence characteristic, Tc values. The mass transfer coefficients and dimensionless turbulence characteristic values were highest at the bath surface and near plume region. The values decreased in identified dead zones in the regions close to the circular side walls of the model. The results revealed that the mass transfer coefficients and turbulence characteristics were different with respect to different submergence levels of the compacts. These findings lead to the conclusion that the fluid flow was stratified within the vessel.